Reconstruction of the first version Borys Liatoshynsky’s Third symphony: questions and answers (on the material of the third movement) - Fareniuk, Hlib (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2023)
Relevance of the study. Borys Liatoshynsky’s Third symphony is one of the most famous compositions of Ukrainian symphonic music. The work’s first version (1951) was subjected to devastating ideological criticism, after the creation of its second version (1954) and its premiere in December 1955, it was recognized as one of the composer’s greatest creative achievements. It was traditionally considered that the second version of the Third Symphony differs from the first version only in its finale (fourth movement). In the article unknown fragments of the Symphony’s score are analysis, which were recently found in the archive of Boris Liatoshynsky’s Cabinet-Museum. These fragments appearance assumes a rethinking of the traditional approach to the issue of versions of the Third Symphony. The purpose of the article is to introduce new archival finds into scientific circulation and to revise the established view of the first version of Borys Liatoshynsky’s Third Symphony. Methods. In the article historical, comparative and textual research methods are used. The results and conclusions. The issue of differences between the versions of Borys Liatoshynsky’s Third symphony has been resolved in different ways in the musicological literature. N. Zaporozhec (1960) and A. Yefimenko (2016) pointed out the difference in the finals; V. Samohvalov (1981) and M. Hordiichuk (1969) wrote that the composer made changes in the third and fourth movements; Yu. Hozhyk (1997), in the most detailed study to date, stated about edits in all parts of the symphonic cycle. Found fragments from the score of the first version of the Symphony make it possible to clarify this contradictory situation. In a letter to R. Gliere, dated September 1, 1954, Boris Liatoshynsky described in detail the changes made for the second version of the Symphony: the first movement was almost not edited, the second was shortened, in the third (scherzo) movement composer changed the trio, and the finale was thoroughly reworked. On four pages of the score found in the composer’s Cabinet-Museum one can see the trio from the third movement of the Symphony in the first version. It was significantly less than what we know from the second version (17 bars instead of 80). After composing the new trio, Liatoshynsky made almost no changes for the score of the second version (the development section was shortened by 1 bar, the code—by 5 bars). These changes in purely immanent musical solutions have a direct impact on the general concept of the Symphony cycle, so it would be fair to note that the difference between the two versions presents two different solutions to the collision of the Third Symphony.